2000
DOI: 10.1007/s12110-000-1010-6
|View full text |Cite
|
Sign up to set email alerts
|

Parental investment, self-control, and sex differences in the expression of adhd

Abstract: Women do most of the parenting. To provide a stable and healthier setting for children they must sublimate their own interests and feelings, which puts greater pressures on women to communicate needs clearly or to be deceptive when the occasion demands. The likely advantage in communication skills and self-control may ameliorate the impact of disorders like ADHD where the most serious deficit is in self-inhibition. This would account for the strikingly uneven male to female sex ratio of 2:1 (in epidemiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Analogous to both Tourette syndrome and OCD, symptom severity in ADHD has been found to correlate negatively with hippocampal volumes (Peterson et al, 2007; Plessen et al, 2006), findings that have been attributed to a hippocampal-based compensatory response (Peterson et al, 2007; Plessen et al, 2006). Also as with Tourette syndrome and OCD, females with ADHD seem to have less severe symptoms at higher than at lower estrogen points in the menstrual cycle (Quinn, 2005; Stevenson and Williams, 2000). Although less research has been carried out on DCD, one recent fMRI study of motor function found increased MTL (parahippocampal) activation in children with DCD as compared to typically developing peers, despite equivalent performance (Zwicker et al, 2010), suggesting the possibility of declarative memory-based compensation of motor function in this disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Analogous to both Tourette syndrome and OCD, symptom severity in ADHD has been found to correlate negatively with hippocampal volumes (Peterson et al, 2007; Plessen et al, 2006), findings that have been attributed to a hippocampal-based compensatory response (Peterson et al, 2007; Plessen et al, 2006). Also as with Tourette syndrome and OCD, females with ADHD seem to have less severe symptoms at higher than at lower estrogen points in the menstrual cycle (Quinn, 2005; Stevenson and Williams, 2000). Although less research has been carried out on DCD, one recent fMRI study of motor function found increased MTL (parahippocampal) activation in children with DCD as compared to typically developing peers, despite equivalent performance (Zwicker et al, 2010), suggesting the possibility of declarative memory-based compensation of motor function in this disorder.…”
Section: Discussionmentioning
confidence: 99%
“…This likely reflects, at least partially, a different hormonal milieu (Stevenson and Williams, 2000).…”
mentioning
confidence: 99%
“…AD/HD has one of the highest heritabilities for a ''trait,'' averaging 0.64-0.91 (Edelbrock et al, 1995;Gillis et al, 1992;Levy et al, 1997;Zahn-Waxler et al, 1996). The models that attempt to explain this disorder argue that AD/HD likely reflects reduced efficiency in executive functions, particularly self-regulation (impulse control) (Baird et al, 2000;Barkley, 1997aBarkley, ,b, 2001Stevenson and Williams, 2000) and/or deficiencies in reward mechanisms (Blum et al, 2000), or both (Sonuga-Barke, 2002).…”
mentioning
confidence: 99%